Is there a trade-off in resource allocation to condensed tannins and thorn defences in Vachellia (Acacia) species?. Issue 4 (1st October 2016) - Sebata, Allan
Abstract : Acacia species invest in condensed tannins (CT) and thorn defences among others. Plant defences are considered costly because they use resources that would otherwise be available for growth and reproduction. To reduce plant defence costs it has been argued that there are trade-offs between different types of defences. I tested for a trade-off between CT and thorn defences in Vachellia ( Acacia ) species. Thorn defences were expressed as thorn biomass, thorn density and thorn length. The relationship between defences was tested using Pearson correlation in addition to that with leaf area. My results support a trade-off between CT and thorn biomass and thorn density but not thorn length. Vachellia karroo ( Acacia karroo ) had high CT but low thorn biomass and thorn density, whereas V. gerrardii ( A. gerrardii ) had low CT but high thorn biomass and thorn density. Thorn length was positively correlated with CT and negatively related to thorn biomass and thorn density. Leaf area had a strong positive correlation with thorn biomass and thorn density, a weak negative relationship with CT, and a non-significant correlation with thorn length. I conclude that CT has a strong trade-off with thorn biomass and thorn density but not thorn length.